The Political Direction Of The Law On The Establishment Of The Capital City Of Nusantara: Analysis Of Interests, Public Participation, And Regulatory Legitimacy - Khairunnisa, Maulida (Ipso Jure, 2025)
This article examines the legal politics of Indonesia’s new capital, Ibu Kota Nusantara, by analyzing political interests, public participation, and the regulatory legitimacy of Law No. 3 of 2022. Using a normative juridical method, combined with constitutional and administrative law analysis, the study reveals that the formation of the IKN Law reflects strong executive centralization and strategic political objectives that influence the institutional design of the IKN Authority. Despite its national strategic status, the legislative process displayed limited transparency, minimal stakeholder involvement, and accelerated deliberation, raising concerns regarding compliance with constitutional participatory standards. The exceptional governance structure granted to the IKN Authority also presents challenges related to democratic accountability, land governance discretion, environmental safeguards, and oversight mechanisms. Procedural deficiencies at the legislative stage risk generating long-term legitimacy deficits that may extend into derivative regulations governing land use, investment, and environmental management. The study concludes that while the IKN project is framed as a transformative development agenda, its regulatory framework requires stronger participatory mechanisms, clearer oversight structures, and enhanced protections for local and indigenous communities to ensure long-term constitutional and political legitimacy.